Distinguishing Radiculopathies from Mononeuropathies - Robblee, Jennifer; Katzberg, Hans (Frontiers in Neurology, 2016)
Identifying “where is the lesion” is particularly important in the approach to the patient with focal dysfunction where a peripheral localization is suspected. This article outlines a methodical approach to the neuromuscular patient in distinguishing focal neuropathies versus radiculopathies, both which are common presentations to the neurology clinic. This approach begins with evaluation of the sensory examination to determine whether there are irritative or negative sensory signs in a peripheral nerve or dermatomal distribution. This is followed by evaluation of deep tendon reflexes to evaluate if differential hyporeflexia can assist in the two localizations. Finally, identification of weak muscle groups unique to a nerve or myotomal pattern in the proximal and distal extremities can most reliably assist in a precise localization. The article concludes with an application of the described method to the common scenario of distinguishing radial neuropathy versus C7 radiculopathy in the setting of a wrist drop and provides additional examples for self-evaluation and reference. The current approach uses the the basics of the neurological examination in a unique way that can be used by a various clinicians to localize these common neuromuscular processes. The learner can then build on this structured approach when encountering more complex neuromuscular presentations, including localizing less common mononeuropathies or plexopathies.